2022
DOI: 10.1155/2022/3743588
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the Demand for Continuing Education of Nurses in the Department of Infectious Diseases and Its Influencing Factors

Abstract: Infection department is unique in working hours, environment, content, methods, and skills requirements, and continuing education plays an important role in stabilizing and improving the professional level of nurses in the infection department. Understanding the needs of nurses in the infection department for continuing education and the possible influencing factors of participating in continuing education and providing a management basis for managers in a targeted way can make the role of continuing education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In this challenging environment, staff, such as teachers, clinicians, etc., had to put in a lot of effort to get promoted to higher-level professional titles, which generated staff with junior titles reporting serious role conflict and job burnout. [ 9 , 18 ] Moreover, professional theory, logical thinking, and clinical/teaching experience of clinical teachers with lower professional titles were relatively deficient, [ 19 ] which further increased the level of role conflict. The study indicated that, in hospitals, those with higher professional titles were more likely to have the right to allocate human resources reasonably and have more free time to complete the teaching plan, thus resulting in a lower level of role conflict.…”
Section: Discussionmentioning
confidence: 99%
“…In this challenging environment, staff, such as teachers, clinicians, etc., had to put in a lot of effort to get promoted to higher-level professional titles, which generated staff with junior titles reporting serious role conflict and job burnout. [ 9 , 18 ] Moreover, professional theory, logical thinking, and clinical/teaching experience of clinical teachers with lower professional titles were relatively deficient, [ 19 ] which further increased the level of role conflict. The study indicated that, in hospitals, those with higher professional titles were more likely to have the right to allocate human resources reasonably and have more free time to complete the teaching plan, thus resulting in a lower level of role conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Their work underscores the importance of ongoing professional development to enhance healthcare delivery practices and patient outcomes. [8] In sum, the reviewed literature demonstrates the multifaceted applications and benefits of continuing education across diverse contexts, ranging from healthcare to broader educational landscapes. It underscores the imperative of tailored and targeted continuing education programs to address the unique needs of various populations and professions, thereby contributing to enhanced practice and policy within respective fields.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%